Effect of 52-week liraglutide treatment on diabetes risk and glycaemic control in women with obesity and prior gestational diabetes. A randomized, double-blind, placebo-controlled study - Perämäki, Roosa; Ollila, Meri-Maija; Hukkanen, Janne; Vääräsmäki, Marja; Uotila, Jukka; Metso, Saara; Hakkarainen, Heidi; Rintamäki, Reeta; Löyttyniemi, Eliisa; Immonen, Heidi; Kaaja, Risto (Elsevier, 2025)
Aims:
We investigated the effect of 52-week liraglutide treatment on the incidence of type 2 diabetes (T2D) compared with placebo treatment in women with obesity and previous gestational diabetes (pGDM) requiring medical treatment. As secondary outcomes, the prevalence of prediabetes and glycaemic control were investigated.
Methods:
Women were randomized to once daily subcutaneous liraglutide 1.8 mg or placebo for 52 weeks. Oral glucose tolerance test, C-peptide, insulin, HbA1c and lipids were determined at baseline, 26 weeks, and 52 weeks.
Results:
In total, 75 women [mean age of 34.5 years, median BMI of 38.0 kg/m2] were assigned to liraglutide (n = 37) or placebo (n = 38). At 52 weeks, T2D was diagnosed in 3% (n = 1) of the liraglutide group and 8% (n = 2) of the placebo group (p = 0.58), and prediabetes in 27% (n = 9) and 58% (n = 15), respectively (p = 0.032). In intention-to-treat analysis, 52-week liraglutide treatment reduced fasting glucose [group × time interaction p = 0.0047; estimated treatment difference (ETD) at 52 weeks −0.5 mmol/L, p = 0.0020], HbA1c [p = 0.020; ETD -0.2% (−2.1 mmol/mol), p = 0.056], weight (p = 0.0087; ETD -6.2 kg, p = 0.20) and waist circumference (p = 0.022; ETD -3.9 cm, p = 0.25), and improved Matsuda index (p = 0.049; ETD 0.7, p = 0.011) compared with placebo.
Conclusions:
Liraglutide reduces the prevalence of prediabetes and improves glycaemic control in women with obesity and pGDM. Due to few T2D cases, the effect of liraglutide on diabetes risk could not be reliably assessed.